2015
DOI: 10.1109/tste.2015.2457917
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Dynamic Spatial Correlations of Geographically Distributed Wind Farms and Constructing Ellipsoidal Uncertainty Sets for Optimization-Based Generation Scheduling

Abstract: The correlation information is very important for system operations with geographically distributed wind farms, and necessary for optimization-based generation scheduling methods such as the robust optimization (RO). The purpose of this paper is to provide the dynamic spatial correlations between the geographically distributed wind farms and apply them to model the ellipsoidal uncertainty sets for the robust unit commitment model. A stochastic dynamic system is established for the distributed wind farms based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…Although Beta distribution cannot model the fat tail of the forecast errors perfectly [38], due to its variable kurtosis [38], it is still more suitable than the Gaussian distribution and gives reasonably accurate results [38,39]. Beta PDF has been used in many recent studies [40][41][42][43] and therefore is chosen in this paper to represent wind power forecast errors. The PDF of the Beta distribution is defined as [36]:…”
Section: Scenario Generationmentioning
confidence: 99%
“…Although Beta distribution cannot model the fat tail of the forecast errors perfectly [38], due to its variable kurtosis [38], it is still more suitable than the Gaussian distribution and gives reasonably accurate results [38,39]. Beta PDF has been used in many recent studies [40][41][42][43] and therefore is chosen in this paper to represent wind power forecast errors. The PDF of the Beta distribution is defined as [36]:…”
Section: Scenario Generationmentioning
confidence: 99%
“…Literature [11,12] analyzed the WSC in different terrain conditions including hillsides, valleys, airports, pastures and houses, coasts, rugged terrain, the junction between grassland and forest, it is concluded that the WSC is stronger where the terrain is more flat with less obstacle, and the correlation is the strongest at the coast, the weakest in the mountains. Advanced application based on WSC is a research hotspot around the world, mainly researching its applications in wind turbine equivalent modeling [11][12][13], wind power prediction [14,15], power flow calculation [16,17] and wind power integration stability assessment [18,19], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In past years, the study of correlation of wind speed and wind power in wind farms which was applied in unit commitment [7], reliability evaluation [8], and economic dispatch and so on [9] has provided important insights for power system planning and operation. Though some achievements have been made with general knowledge of correlation characteristics in wind speed or wind power, researchers have only focused on the relationships at the wind farm or wind site levels [10,11] but failed to consider the internal relationship among wind turbines located in the same wind farms.…”
Section: Introductionmentioning
confidence: 99%